Tanycytes allow a tight BBB in the median eminence - Rodriguez, Esteban; Blazquez, Juan Luis; Guerra, Montserrat (Henry Stewart Talks, 2008)
The blood-brain barrier (BBB), Organization of the BBB in the Median Eminence, Structure, function and subtypes of tanycytes, Horseradish peroxidase and trypan blue as compartment markers, Leptin and tanycytes in the hypothalamus
Updated at 2018/04/03